2023
DOI: 10.3390/toxics11030223
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas–Liver–Adipose Axis: Target of Environmental Cadmium Exposure Linked to Metabolic Diseases

Abstract: Cadmium has been well recognized as a critical toxic agent in acute and chronic poisoning cases in occupational and nonoccupational settings and environmental exposure situations. Cadmium is released into the environment after natural and anthropogenic activities, particularly in contaminated and industrial areas, causing food pollution. In the body, cadmium has no biological activity, but it accumulates primarily in the liver and kidney, which are considered the main targets of its toxicity, through oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 283 publications
0
8
0
Order By: Relevance
“…Long-term cadmium exposure depletes muscle and liver glycogen due to its effects on the enzymes associated with glycogenesis and energy metabolism ( Moroni-González et al, 2023 ), as well as harms the kidney and liver through oxidative stress ( Ebrahimi et al, 2023 ). Also, Cadmium advances osteoporosis, leukemia, hypertension, diabetic renal complications, and living organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term cadmium exposure depletes muscle and liver glycogen due to its effects on the enzymes associated with glycogenesis and energy metabolism ( Moroni-González et al, 2023 ), as well as harms the kidney and liver through oxidative stress ( Ebrahimi et al, 2023 ). Also, Cadmium advances osteoporosis, leukemia, hypertension, diabetic renal complications, and living organisms.…”
Section: Resultsmentioning
confidence: 99%
“…It can be bio-enriched in different species along the food chain and eventually accumulates in human and animal livers [20]. Lut is a natural avonoid with various pharmacological activities [21,22]. Although previous research has shown the therapeutic property of Lut against Cd-induced in ammation, whether Lut has a mitigating effect on Cd-induced liver injury remains unknown [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The 20th century witnessed a disturbing increase in heavy metal toxicity . The extensive environmental distribution of cadmium has heightened concerns regarding its disproportionate toxicity and adverse ecological consequences. , Notably, Cd accumulates significantly in hepatic and renal tissues, initiating severe cellular damage across multiple organ systems. , Cd finds widespread application in various industrial sectors, including paint manufacturing, silver-plating, battery production, and agricultural practices . Cigarette smoke is a well-recognized source of Cd exposure, significantly elevating the risk of contact .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Notably, Cd accumulates significantly in hepatic and renal tissues, initiating severe cellular damage across multiple organ systems. 8 , 9 Cd finds widespread application in various industrial sectors, including paint manufacturing, silver-plating, battery production, and agricultural practices. 6 Cigarette smoke is a well-recognized source of Cd exposure, significantly elevating the risk of contact.…”
Section: Introductionmentioning
confidence: 99%